Popular oriental compact dictionary english to urdu(with urdu pronunciation) (Oriental book society Lahore)
Especially written to support the language and literacy needs of children aged 6+, this dictionary introduces features such as showing parts of speech (noun, verb, adjective or adverb) and other forms of a word (plurals or past tense of a verb)